PENGARUH PERSONAL SELLING CUSTOMER SERVICE TERHADAP KEPUASAN NASABAH DI PT. BANK RAKYAT INDONESIA (Persero) Tbk CABANG PALU - Yulianti, Riscy (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
Marketing promotion is an effort to convey messages or information to the public, especially customers, regarding the existence of a product or service. All efforts in dealing with such complex problems and such sharp competition through various ways and methods by decision makers in a company, especially in facing the current high level of competition, are implementing the right promotional mix, one of which is personal selling. At a time when the competitive situation is so tight, personal selling is a special concern for the management of companies engaged in the production of goods and services. In the world of banking, promotion in marketing bank products through personal selling is one of the most important things to introduce the products offered to the public or customers. In the world of banking, customer service is an important thing, namely dealing with customers directly, one of the tasks of customer service is serving all customer needs satisfactorily. The services provided include receiving complaints or problems being faced by customers. Customer satisfaction is the most important thing for service providers, because customers will spread their feelings of satisfaction to potential customers if the customer gets a good impression or service from the service provider, which will increase the reputation of the service provider.